2017
DOI: 10.3945/an.117.015446
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Indicators as Body Fat Discriminators in Children and Adolescents: A Systematic Review and Meta-Analysis

Abstract: We analyzed the discriminatory capacity of anthropometric indicators for body fat in children and adolescents. This systematic review and meta-analysis included cross-sectional and clinical studies comprising children and adolescents aged 2-19 y that tested the discriminatory value for body fat measured by anthropometric methods or indexes generated by anthropometric variables compared with precision methods in the diagnosis of body fat [dual-energy X-ray absorptiometry (DXA), computed tomography, air displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 19 publications
2
38
1
4
Order By: Relevance
“…The review performed by Junior [10] concludes that BMI, waist circumference, and waist-to-height ratio are body fat discriminators in children and adolescents with low operational costs. Another study performed by Sardinha [20] suggests that triceps fold gives the best result in order to define the relationship between BMI and percentage of body fat in healthy boys and girls aged 10 to 15 years, whereas BMI and upper arm girth are reasonable second choices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The review performed by Junior [10] concludes that BMI, waist circumference, and waist-to-height ratio are body fat discriminators in children and adolescents with low operational costs. Another study performed by Sardinha [20] suggests that triceps fold gives the best result in order to define the relationship between BMI and percentage of body fat in healthy boys and girls aged 10 to 15 years, whereas BMI and upper arm girth are reasonable second choices.…”
Section: Discussionmentioning
confidence: 99%
“…Another study performed by Sardinha [20] suggests that triceps fold gives the best result in order to define the relationship between BMI and percentage of body fat in healthy boys and girls aged 10 to 15 years, whereas BMI and upper arm girth are reasonable second choices. Both studies suggest specific cutoffs by age group and sex; however, these parameters should be utilized with caution in the evaluation of young athletes [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In infants (1, 4, and 7 months old), Bell et al [39] found that BMI is limited as a surrogate for adiposity and (especially) adiposity changes. However, there is still controversy [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Body composition measurement tools and machines have better accuracy, but are more expensive and their usage is mostly limited to research purposes. 12,13 In addition, bioelectrical impedance analysis (BIA), a body composition measurement tool to assess fat distribution, is accurate, easy to use, comfortable for subjects, and relatively affordable. 13 Body fat and fat distribution are determining factors of menarcheal age that can be modified through lifestyle changes.…”
mentioning
confidence: 99%